Role of Student Personal Characteristics in Development and Implementation of Innovations; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Bureeva M. S. Margarita Sergeevna (2017, 2017)
Title screen